The Disturbing Effect of Neuromuscular Fatigue on Postural Control Is Accentuated in the Premenstrual Phase in Female Athletes - Kacem, Maissa; Borji, Rihab; Sahli, Sonia; Rebai, Haithem (Frontiers in Physiology, 2021)
This study explored the fatigue effect on postural control (PC) across menstrual cycle phases (MCP) in female athletes. Isometric maximal voluntary contraction (IMVC), center of pressure sway area (CoParea), CoP length in the medio-lateral (CoPLX) and antero-posterior (CoPLY) directions and the Y-balance test (YBT) were assessed before and after a fatiguing exercise during the follicular phase (FP), mid-luteal phase (LP) and premenstrual phase (PMP). Baseline normalized reach distances (NRD) for the YBT were lower (p=0.00) in the PMP compared to others MCP, but the IMVC, CoParea, CoPLX and CoPLY remained unchanged. After exercise, the IMVC and the NRD decrease was higher at PMP compared to FP (p=0.00) and LP (p=0.00). The CoParea, CoPLX and CoPLY increase was higher in the PMP compared to FP (p=0.00) and LP (p=0.00). It was concluded that there is an accentuated PC impairment after exercise observed at PMP.